Modeling the response of within-storm runoff and erosion dynamics to climate change in two Mediterranean watersheds: A multi-model, multi-scale approach to scenario design and analysis - Nunes, J. P.; Seixas, J.; Keizer, J. J. (CATENA, 2013)
Climate change in the Mediterranean is expected to lead to lower total rainfall and soil moisture, together with higher storm intensities; different vegetation types are expected to react positively or negatively to these and other changes. Climate change could therefore have positive or negative impacts on runoff and soil erosion during storms, and previous research has indicated that the impacts could be different at the field, hillslope and catchment scales. This problem was assessed for two Mediterranean watersheds by a combined application of the PROMES regional climate model, the SWAT continuous hydrological and vegetation model, and the MEFIDIS storm runoff and erosion model. PROMES results were used to estimate changes to storm rainfall intensity, while SWAT was applied with the PROMES results to estimate changes to soil moisture and saturation deficit, as well as vegetation cover. The results from both models were used to generate scenarios of changes to storm intensity (increasing), saturation deficit (increasing) and vegetation cover (increasing according to vegetation type). These scenarios were used as input for the MEFIDIS model to study the impacts of these changes on runoff and soil erosion across spatial scales for a set of storms. The simulation results indicate that (i) the increase in saturation deficit and vegetation cover is sufficient, in many cases, to decrease or counterbalance the impacts of increased storm intensity on soil erosion at all spatial scales; (ii) catchment sediment yield is noticeably more sensitive to the climate change scenarios than within-watershed soil erosion, mostly due to the impacts of changes to saturation deficit and vegetation cover on connectivity; (iii) within the watershed, impacts on soil erosion vary with landcover type, with croplands suffering the most negative impacts.
Keywords: climate change; Mediterranean watersheds; Modeling; soil erosion

GeneticLand: modelling land-use change using evolutionary algorithms - Seixas, J.; Nunes, J. P. (Modelling Land-Use change, 2007)
Future land-use configurations provide valuable knowledge for policy makers and economic agents, especially under expected environmental changes such as decreasing rainfall or increasing temperatures. This chapter proposes an optimisation approach for modelling land-use change in which landscapes (land uses) are generated through the use of an evolutionary algorithm called GeneticLand. It is designed for a multiobjective function that aims at the minimisation of soil erosion and the maximisation of carbon sequestration, under a set of local restrictions. GeneticLand has been applied to a Mediterranean landscape, located in southern Portugal. The algorithm design and the results obtained show the feasibility of the generated landscapes, the appropriateness of the evolutionary methods to model land-use changes and the spatial characteristics of the landscape solutions that emerge when physical drivers have a major influence on their evolution.
The following values have no corresponding Zotero field: periodical: Modelling Land-Use change
Keywords: climate change; evolutionary computing; land use; long-term; Mediterranean landscape.; optimisation; Spatial planning